PERAN TEKNOLOGI FINANSIAL, LITERASI FINANSIAL DAN INKLUSI FINANSIAL TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH MELALUI EFEKTIFITAS PENGELOLAAN KEUANGAN DAERAH DI KABUPATEN BONDOWOSO - Kurniawan, Didik; Ariyantiningsih, Febri; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2024)
Increasing local revenue is a capital needed to achieve regional development goals successfully because Regional Original Revenue defines the ability of the region to carry out government functions in both public services and development. This study aimed to determine the role of Financial Technology, Financial Literacy, and Financial Inclusion in increasing Regional Original Revenue through the effectiveness of regional financial management in Bondowoso Regency. The sampling technique used in this study was Saturated Sampling. This study's data analysis and hypothesis testing used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.2.8 application show that financial technology has a significant positive effect on the effectiveness of regional financial management, financial literacy has a significant positive effect on the efficacy of regional financial management, financial inclusion has no significant effect on the effectiveness of regional financial management, financial technology has no significant impact on increasing local revenue, financial literacy has a significant effect on increasing local revenue, financial inclusion has a significant effect on increasing local revenue, the effectiveness of regional financial management has no significant effect on improving local revenue.